A 13-dB IIP3 improved low-power CMOS RF programmable gain amplifier using differential circuit transconductance linearization for various terrestrial mobile D-TV applications. - Tae Wook Kim (IEEE Journal of solid state circuits)
A CMOS RF digitally programmable gain amplifier (RF PGA), covering various terrestrial mobile digital TV standards (DMB, ISDB-T, and DVB-H) is implemented as a part of a low-IF tuner IC using 0.18-μm CMOS technology. An improvement of 13-dB IIP3 is attained without significant degradation of other performance criteria like gain, noise figure, common-mode rejection ratio, etc., at similar power consumption. This is achieved by applying a newly proposed differential circuit gm" (the second derivatives of transconductance) cancellation technique, called the differential multiple gated transistor (DMGTR). In the DMGTR amplifier, the negative value of gm" in the fully differential amplifier can be compensated by the positive value of gm" in the pseudo differential amplifier which is properly sized and biased. By adopting the DMGTR, a low-power highly linear RF PGA is implemented. Also, in order to have wide gain range with fine step resolution, a new RF PGA architecture is proposed. The measurement results of the proposed RF PGA exhibit 50-dB gain range with 0.25-dB resolution, 4.5-dB noise figure, a -4-dBm IIP3 (maximum 30 dBm) and 25-dB gain at 16-mW power consumption.